PENGARUH PERFORMANCE EXPECTATION, EFFORT EXPECTANCY, SOCIAL INFLUENCE, PERCEIVED RISK, PERCEIVED COST PADA MINAT MENGGUNAKAN MOBILE PAYMENT DI INDONESIA - Marheni Eka Saputri (Fakultas Seni Rupa dan Desain ITB, 2022)
The development of technology and information systems continues to give birth to various innovations, especially those related to financial technology (fintech) in order to meet the needs of society, including in the field of payment system services. Indonesia has several major players in fintech but non-cash transactions via fintech are only 1.66% of the circulation of money in Indonesia. According to Mckinsey, fintech penetration in Indonesia has only reached 5%. This figure is much lower than other countries. Mobile Payment, or abbreviated as M-Payment, is a payment method using a mobile phone or cellphone as the means. Payment fintechs including LinkAja, Go-Pay, OVO, and DANA are expected to target users in remote areas of the archipelago. However, it cannot be denied that there are still Indonesians who use ordinary cell phones or have not access to the internet. Moreover, based on Statista data, smartphone users are projected to only reach 28% of Indonesia's total population this year. Looking at this data, we can assume that the market potential for mobile money in Indonesia is quite large, but the market penetration is still low. Based on this background, it can be seen that the intention to adopt mobile payments is still very low. The behaviors that factor into the intention to adopt technology are performance expectancy, effort expectation, social influence, perceived risk, and perceived cost. The purpose of this study was to see how the effect of performance expectancy, effort expectation, social influence, perceived risk, and perceived cost on the intention to use mobile payments in Indonesia. This research was conducted on 400 respondents using Structural Equation Model analysis (SEM PLS). Keywords: Intention to use, Mobile Payment, SEM PLS, UTAUT.